Improving resource targeting in Niger: Joint financial analysis and food system mapping - Ulimwengu, John M.; Gbossa, Nadine (International Food Policy Research Institute, 2024)
This policy brief combines the results of a food system mapping exercise with an analysis of financial flows into Niger’s food system from 2019 to 2022 to inform policymaking for food system transformation. The food system mapping reveals several critical points of failure, from low agricultural productivity and inefficient supply chains to poor nutritional outcomes and environmental degradation. Analysis of domestic and international financial flows to the food system reveals that climate adaptation and nutrition are underfunded areas. Understanding these weaknesses can help policymakers and development partners take a more coordinated and strategic approach to addressing the challenges facing Niger’s food system and can inform more effective resource allocation, ensuring that resources support long-term food security and sustainability.